The fundamentals of hedge fund management - Strachman, Daniel A., 1971- (Wiley finance series., 2012)
Updated edition of the book that gives investors, advisors, and managers the tools they need to launch and maintain a hedge fund in today's economy The hedge fund industry has gone through dramatic changes in recent years. Investors of all types continue to want to place their assets into these investment vehicles even in the wake of the credit crisis, massive frauds, and insider trading scandals. Once the forbidden fruit of Wall Street, hedge funds are now considered "must have" investments in any diversified portfolio. Now in its second edition, The Fundamentals of Hedge Fund Management is r.